The Real Effects of Bank Capital Requirements - Fraisse, Henri; Lé, Mathias; Thesmar, David (Management Science, 2020)
We measure the impact of bank capital requirements on corporate borrowing, investment, and employment using loan-level data. The Basel II regulatory framework makes capital requirements vary across both banks and firms, which allows us to control for time-varying firm-level risk and bank-level credit supply shocks. We find that a 1 percentage point increase in capital requirements reduces lending by 2.3%–4.5%. Firms can attenuate this reduction by substituting borrowing across banks, but only to a limited extent. The resulting reduction in borrowing capacity affects significantly both investment and employment: for firms whose effective capital requirements increase by 1 percentage point, fixed assets are reduced by 1.1%, capital expenditures by 2.7%, and employment by 0.8%. This paper was accepted by Tomasz Piskorski, finance.